Comparison of keratometric and pachymetric parameters with Scheimpflug imaging in normal and keratoconic Asian eyes - Lim HB (Dove Medical Press, 2014)
Hou-Boon Lim,1 Gavin Tan,1 Li Lim,1 Hla Myint Htoon2 1Singapore National Eye Centre, Singapore; 2Singapore Eye Research Institute, Singapore Purpose: To evaluate the keratometric and pachymetric parameters of keratoconic corneas of Asian eyes with the Scheimpflug imaging camera. Patients and methods: This is a cross-sectional study of 22 eyes with Amsler-Krumeich stage 1 keratoconus and 48 eyes from normal subjects conducted in a tertiary eye hospital. A rotating Scheimpflug imaging system, the Pentacam, was used to evaluate all eyes for tomographic parameters, as well as pachymetric progression indices (PPI) and Ambrósio relational thickness (ART). Results: All PPI and ART parameter values were significantly different between study and control groups. Cornea minimum radius of curvature, absolute distance from corneal apex to thinnest location, as well as the distance from corneal apex to thinnest location in Y-axis also demonstrated statistically significant differences. The mean ART values for keratoconus eyes were 241 µm (ART-maximum) and 352 µm (ART-average), falling within previously reported best cutoff values for detecting keratoconus. On receiver operating characteristics curve analysis, the area under the curve values were highest for PPI and ART parameters. Conclusion: There are significant differences in tomographic parameters between stage 1 keratoconic and normal Asian eyes. Pachymetric indices such as the PPI and the ART index can serve as additional tools in differentiating keratoconic from normal eyes. The findings validate the usefulness of the ART in identifying keratoconic eyes in Asians. Keywords: keratoconus, pentacam, corneal tomography, Ambrósio relational thickness